Policy Effectiveness of Loan for Delaying Timber Harvesting for Smallholder Private Forest in Indonesia - Bramasto Nugroho; Sudarsono Soedomo; Ahmad Dermawan (Institut Pertanian Bogor (IPB University), 2017)
This study aimed to analyze policy effectiveness of loan for delaying timber harvesting for smallholder private forest business (Pinjaman Tunda Tebang Hutan Rakyat; hereinafter will be referred as PTT-HR). The analysis will be used to provide recommendations for improving PTT-HR scheme included scaling out and scaling up of the scheme for improving economic benefits and supporting smallholder private forest business as well as for strengthening farmer’s welfare. Field survey was conducted in October–November 2013 in two districts in Central of Java, Indonesia namely Blora and Wonosobo District as recipient of PTT-HR from Public Service Agency for Forest Development Financing Center (BLU Center of P2H) Ministry of Forestry, Republic of Indonesia. The results showed that PTT-HR policy has implemented effectively based on evaluation parameter derived from the objectives of policy namely the age of the stands for loan collateral, the capabilities for improving farmer’s welfare, utilization of loan, perception of the farmers regarding to the ease of the process and purpose of loan utilization, and the capability of loan repayment. However, this research has not been answered the aspect of PTT-HR policy implementation efficiency.